Conference Topic (EAAE Annual Conference Proceedings, 2023)
We feel we are at the start of new dimensions of our profession. The increase in scale and the overlapping of disciplines in the fields of architecture – urbanism – landscape architecture in current practice needs to be reflected in current education.